1995
DOI: 10.1006/viro.1995.1133
|View full text |Cite
|
Sign up to set email alerts
|

Genome Structure and Phylogenetic Analysis of Lettuce Infectious Yellows Virus, a Whitefly-Transmitted, Bipartite Closterovirus

Abstract: We report the complete nucleotide sequences of lettuce infectious yellows virus (LIYV) RNAs 1 and 2. LIYV RNA 1 is 8118 nucleotides and includes three open reading frames (ORFs). Computer-assisted analysis of LIYV RNA 1 ORFs identified domains for a papain-like protease, methyltransferase (MTR), RNA helicase (HEL), and RNA-dependent RNA polymerase (RdRp). We suggest that the RdRp domain is expressed independently of the other replication-associated domains via a + 1 ribosomal frameshift. Amino acid sequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
127
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(133 citation statements)
references
References 0 publications
5
127
0
1
Order By: Relevance
“…A. Agranovsky W. Jelkmann, B. Fechtner and A. A. Agranovsky closterovirus genomes have revealed no statistically significant similarity among them, apart from the C-terminal PCP domain (Karasev et al, 1995 ;Klaassen et al, 1995). Our analysis also failed to identify any related sequences in the LChV and BYV proteins upstream of their PCP (Fig.…”
mentioning
confidence: 65%
See 4 more Smart Citations
“…A. Agranovsky W. Jelkmann, B. Fechtner and A. A. Agranovsky closterovirus genomes have revealed no statistically significant similarity among them, apart from the C-terminal PCP domain (Karasev et al, 1995 ;Klaassen et al, 1995). Our analysis also failed to identify any related sequences in the LChV and BYV proteins upstream of their PCP (Fig.…”
mentioning
confidence: 65%
“…3) showed branching of BYV, BYSV, CTV and LIYV compatible with that in the previous POL reconstructions (cf. Dolja et al, 1994 ;Klaassen et al, 1995). Further, our analysis suggested that the aphid-transmissible BYV, BYSV and CTV, on the one hand, and the whiteflytransmissible LIYV, SPSVV and cucumber chlorotic spot virus (CCSV) and the mealybug-transmissible LChV, on the other, represent two distinct evolutionary lineages (Fig.…”
mentioning
confidence: 71%
See 3 more Smart Citations